Successful High-Risk Pulseless-Balloon Aortic Valvuloplasty Procedure in Uncorrected Pulmonary Atresia with Severe Congenital Aortic Stenosis and Low Left Ventricular Function - Sofia, Sefri Noventi; Bahrudin, Bahrudin; Riwanto, Ignatius; Susanto, Hardhono; Soetadji, Anindita; Baskoro, Adhi Gunawan; Prawara, Ananta Sidhi; Satyagraha, Muhammad Thifan; Kurniawati, Yovie; Prakoso, Radityo (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Pulmonary atresia with ventricular septal defect (PA-VSD) and severe bicuspid aortic stenosis is an uncommon condition that presents significant surgical challenges. The dual obstruction leads to chronic pressure overload, resulting in ventricular hypertrophy and decreased systolic function. A low left ventricular ejection fraction (LVEF) increases the risk of mortality during surgical interventions. Percutaneous balloon aortic valvuloplasty (PBAV) poses additional risks due to the intentional induction of pulselessness during balloon inflation. This case report aims to detail the perioperative management strategies employed during PBAV in a patient with PA-VSD, severe aortic stenosis, and low LVEF.Case: We present a 19-year-old female patient weighing 45 kg with shortness of breath and fatigue. Her oxygen saturation was measured at 90% across all extremities. Electrocardiogram (ECG) findings indicated sinus rhythm with biventricular hypertrophy and incomplete left bundle branch block (LBBB). Chest X-ray revealed cardiomegaly and pulmonary artery dilation, while echocardiography confirmed PA-VSD, severe aortic stenosis with a mean pressure gradient (mPG) of 55 mmHg, and an LVEF of 41.3%. A percutaneous pulseless-BAV was performed using a Tyshak balloon via an antegrade transvenous femoral approach under fluoroscopy and transesophageal echocardiography guidance.Discussion: Anesthesia management focused on gradual medication titration, minimizing patient movement during the procedure, and ensuring comfort due to transesophageal echocardiogram (TEE) probe insertion. A temporary pacemaker was placed in the right ventricular apex for pacing at 220 beats per minute until cardiac arrest occurred post-balloon inflation, and defibrillation successfully restored spontaneous circulation.Conclusion: This case illustrates that PBAV in uncorrected PA-VSD with severe aortic stenosis and low LVEF is feasible despite its inherent risks when conducted by a skilled team utilizing careful judgment throughout the procedure.